2012
DOI: 10.2528/pier11120701
|View full text |Cite
|
Sign up to set email alerts
|

Fields in Fractional Parallel Plate Db Waveguides

Abstract: Abstract-Time harmonic electric and magnetic fields inside a parallel plate DB boundary waveguide are derived and fractional curl operator is utilized to study the fractional parallel plate DB waveguides.The DB boundary conditions are incorporated by assuming the behavior of boundary as perfect electric conductor (PEC) for transverse electric mode and perfect magnetic conductor (PMC) for transverse magnetic mode. For this purpose a general wave propagating inside the parallel plate wave waveguide is assumed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Moreover, the intensities of electric and magnetic fields inside the three-layered parallel plate waveguide are identical for ða ¼ 0; 1Þ but different for the intermediate values, i.e. 0\a\1, which is in agreement with the work by Hussain et al [22], where they showed that electric field distribution in the fractional DB waveguides was similar to that of magnetic field distribution for limiting integer values of the fractional parameter (a ¼ 0; 1), while it was different for the intermediate values, i.e. 0\a\1.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the intensities of electric and magnetic fields inside the three-layered parallel plate waveguide are identical for ða ¼ 0; 1Þ but different for the intermediate values, i.e. 0\a\1, which is in agreement with the work by Hussain et al [22], where they showed that electric field distribution in the fractional DB waveguides was similar to that of magnetic field distribution for limiting integer values of the fractional parameter (a ¼ 0; 1), while it was different for the intermediate values, i.e. 0\a\1.…”
Section: Introductionsupporting
confidence: 90%
“…Field intensity plots for different frequencies are obtained. We present 3D plots of field intensity here, instead of 2D contour plots given by [22], in a related work. The values of parameters are set as d 1 = 0.1 m, d 2 = 0.15 m, and j ¼ 2:5 for chiral nihility waveguide.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fields reflected from each of the three slabs show similar behaviour. Then we extend this work on the layered fractional dual waveguides [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. A wave of general polarization propagating through a parallel plate waveguide is taken, as it is a sum of transverse electric (TE) modes and transverse magnetic (TM) modes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when field is reflected from top and bottom of chiral nihility coated DB interface, it keeps on rotating its plane of polarization and it appears as a circularly polarized field inside the core of the waveguide [68,69]. Fractional dual solutions to the Maxwell equations for fields inside a parallel plate DB waveguide have been discussed by Hussain et al [70].…”
Section: Introductionmentioning
confidence: 99%